Sportif.App as an Effort to Increase Sports Human Resources Readiness and Digitalization of Sports Data Information Management - Fatkhul Imron; Joko Sulistyono; Moh Erkamim; Zandra Dwanita Widodo (International Journal of Economics and Management Research, 2023)
This research is a continuation of community service activities entitled "Introduction and Training of the Sportif.App Application as an Effort to Increase the Readiness of Sports Human Resources and Digitalization of Sports Data Information Management at KONI Surakarta City." Through this tridharma activity, the writing team continued with research aimed at describing and analyzing the benefits of Sportif.App in increasing the readiness of sports human resources through digitizing sports data information management. The research method used is descriptive qualitative which is based on the results of interviews and observations. The Sportif.App application really helps sports human resources by providing data management services that are easy to access and provide information at any time. Administrative requirements can be integrated with sports databases (such as sports, achievements, coaches, referees, etc.), documented, and uploaded through the information system, including verification mechanisms and information about required administrative completeness, as well as monitoring data progress. In this way, sports human resources can work effectively and efficiently in reporting at any time without being limited by time and space. Keywords : Sportif.app, information management, sports data information